Treating Complicated Grief - Simon, Naomi M. (JAMA, 2013)
IMPORTANCE: The death of a loved one is one of life’s greatest, universal stressors to which most bereaved individuals successfully adapt without clinical intervention. For a minority of bereaved individuals, grief is complicated by superimposed problems and healing does not occur. The resulting syndrome of complicated grief causes substantial distress and functional impairment even years after a loss, yet knowing when and how to intervene can be a challenge. OBJECTIVE: To discuss the differential diagnosis, risk factors for and management of complicated grief based on available evidence and clinical observations. EVIDENCE REVIEW: MEDLINE was searched from January 1990 to October 2012. Additional citations were procured from references of select research and review articles. Available treatment studies targeting complicated grief were included. RESULTS: A strong research literature led to inclusion of complicated grief in the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) (termed persistent complex bereavement disorder as a subtype of other specified trauma and stressor-related disorders), although it is a condition for which more research is formally recommended, and there is still ongoing discussion about the optimal name and diagnostic criteria for the disorder. Reliable screening instruments are available, and the estimated prevalence rate is 7% of bereaved people. Randomized controlled data support the efficacy of a targeted psychotherapy including elements that foster resolution of complicating problems and facilitate the natural healing process. Preliminary studies suggest antidepressant medications may be helpful. CONCLUSION AND RELEVANCE: Individuals with complicated grief have greater risk of adverse health outcomes, should be diagnosed and assessed for suicide risk and comorbid conditions such as depression and posttraumatic stress disorder, and should be considered for treatment.